THE MEANING OF SEMANTIC ANALYSIS WITHIN SONG’S LYRICS “A HEAD FULL OF DREAMS” ALBUM BY COLDPLAY - Lilis Sholihah (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2018)
This research is intended to analyze the meanings of semantic and moral values found in songs lyrics in the album by Coldplay. The result of this research is expected to be valuable research in enlarging the knowledge of semantics field especially in analysis of song. In this case the meanings and moral values found in the Coldplay’s Album songs lyrics. In this case, the researcher collects the data in following steps. Firstly, collecting the script of song lyrics taken from the internet. Secondly, assembling data from the sources. Thirdly, reading all the data sources. Lastly, classifying the lyric based on the lexical meaning and moral values and classified them according to the research focus. After analyzing the data, the lexical terms found in this song contains 6 denotations, 5 connotations, 1 ambiguity, 10 antonyms and 11 synonyms. Furthermore, there are many kinds of figurative languages found in some lyrics of the song such as simile, hyperbole, personification, symbol, metaphor, apostrophe, synecdoche, paradox and antithesis, etc. Specifically, the figurative language which found in lyrics a head full of dreams album , there are 1 metaphor, 2 similes, 2 symbol, 2 hyperboles and 1 irony. Then, the five song lyrics in a head full of dreams album by Coldplay tell us about human social life which contained about love, sadness, happiness, spirit and adventure of life.